Evaluating Food Labels and Food Messages: An Experimental Study of the Impact of Message Format and Product Type on Evaluations of Magazine Food Advertisements - Yongick Jeong; Lisa K. Lundy (Journal of Applied Communications, 2015)
This study looked at gain/loss messages in magazine advertisements across three different food products – a fresh, plant-based product (bananas), a processed, plant-based product (potato chips), and a processed, animal-based product (milk). These food products were all unfamiliar brands for the study participants. Using a 2 (gain vs. loss frame) X 3 (organic, non-GMO, and antibiotics free products) mixed-repeated-measures design, this study examines how message format and product type influenced the effectiveness of food labels in magazine food advertisements. Results indicate product type and food labels were more influential than message format (gain/loss frame). Overall, participants viewed organic foods more favorably than non-GMO or antibiotics free foods. Overall, the effect of the gain/loss frames was eclipsed by the effect of the product type and food labels. Participants indicated greater recall for the organic (bananas) message than they did for the antibiotic-free (milk) or GMO (potato chips) messages. The recall also was greater for the food labels found in the organic message. It’s important for food marketers to consider gain/loss frames may be more/less effective depending on the type of food product.
Keywords: Food labels; genetically modified organisms; organic; advertising